Sex-related Anthropometrics in a Lower-Body Mobility Assessment Among Professional Soccer Athletes - Corbin A. Hedt; Jessica T. Le; Tyler Heimdal; Justin Vickery; Erin Orozco; Patrick C. McCulloch; Bradley S. Lambert (North American Sports Medicine Institute, 2022)
# Background The functional movement screen (FMS™) and Y-balance test (YBT) are commonly used to evaluate mobility in athletes. # Purpose The primary aim of this investigation was to determine the relationship between demographic and anthropometric factors such as sex, body composition, and skeletal dimension and scoring on YBT and FMS™ in male and female professional soccer athletes. # Study Design Cross Sectional # Methods During pre-season assessments, athletes from two professional soccer clubs were recruited and underwent body composition and skeletal dimension analysis via dual-energy X-ray absorptiometry (DEXA) scans. Balance and mobility were assessed using the YBT and FMS™. A two-tailed t-test was used to compare YBT between sexes. Chi-square was used for sex comparisons of FMS™ scores. Correlation analysis was used to determine if body composition and/or skeletal dimensions correlated with YBT or FMS™ measures. Type-I error; α=0.05. # Results 40 Participants were successfully recruited: (24 males: 27±5yr, 79±9kg; |16 females: 25±3yr, 63±4kg). YBT: Correlations were found between anterior reach and height (r=-0.36), total lean mass (LM)(r=-0.39), and trunk LM(r=-0.39) as well as between posterolateral reach and pelvic width (PW)(r=0.42), femur length (r=0.44), and tibia length (r=0.51)(all p<0.05). FMS™: The deep squat score was correlated with height(r=-0.40), PW(r=0.40), LM(r=-0.43), and trunk LM (r =-0.40)(p<0.05). Inline lunge scores were correlated with height(r=-0.63), PW(r=0.60), LM(r=-0.77), trunk LM(r=-0.73), and leg LM(r=0.70)(all p<0.05). Straight leg raise scores were correlated with PW (r=0.45, p<0.05). Females scored higher for the three lower body FMS™ measures where correlations were observed (p<0.05). # Conclusions Lower body FMS™ scores differ between male and female professional soccer athletes and are related to anthropometric factors that may influence screening and outcomes for the FMS™ and YBT, respectively. Thus, these anatomical factors likely need to be taken into account when assessing baseline performance and risk of injury to improve screening efficacy. # Level of Evidence Level 3b